Scapular bronchogenic cysts in children: case report and review of the literature - Ozel, SK; Kazez, A; Koseogullari, AA; Akpolat, N (Springer, 2005)
Cutaneous bronchogenic cysts (CBC) are rare solitary lesions which originate from primitive tracheobronchial tree. The periscapular location of these lesions is even a rare condition. The aim of this study is to evaluate this pathology after our case with literature review. An one-year-old girl was brought to our clinics with the complaint of a drainage at the back of her shoulder. In her physical examination, a hyperemic enduration with a sinus and purulent drainage was noted at the left scapular region. Ultrasonography revealed a lesion of 15x11 mm(2) in size with a thick wall and a hypoechoic center. The lumen of the cyst was demonstrated with fistulography. Surgical excision of the lesion was performed and pathological examination revealed a cutaneous bronchogenic cyst. CBC have been reported in 64 cases in the literature. They are often found in the lower neck, sternum and shoulders. They arise due to abnormal bronchial budding during the embryological period. Only in 12 of these patients, including our case, the lesion was located in the periscapular area. Its treatment is surgical because of malignant transformation and infection. The recognition of this entity may help the surgeon for early diagnosis.
22nd Annual Meeting of the Turkish-Association-of-Pediatric-Surgeons -- SEP 08-11, 2004 -- Bursa, TURKEY
Keywords: bronchogenic cyst; cutaneous; scapular; child